Common Infections and Antibiotic Susceptibility among Malnourished Children: A hospital based study from Karachi - Ahmed, Saba (Infectious Diseases Journal of Pakistan, 2023)
Background: The high prevalence of infections among children with severe malnutrition coupled with an atypical clinical presentation justifies the routine use of empirical antibiotic. The choice of antibiotics has to be guided by locally prevalent pathogens and their antibiotic susceptibility patterns. Susceptibilities of organisms keep on changingand require frequent monitoring to keep antibiotics regimen up to date. Aim: This study is aimed at determining prevailing situation of infections and antimicrobial sensitivity of bacteria among malnourished children in peri-urban catchment area of Karachi. Material and Method: This is hospital based retrospective analysis of children from one month to 12 years of age admitted for severe or moderate malnutrition in the pediatric ward of ‘The Indus Hospital’ from October 2010 till July 2011. Culture reports of blood, urine; stool, ear swab and gastric aspirate were analyzed. The Kirby- Bauer diffusion method was used to check isolates susceptibility. Commonly prescribed antibiotics were graded as sensitive or resistant according to standardized charts of Clinical and laboratory standard institute (CLSI) 2012 guidelines. Results: Total of 260 severely malnourished children were enrolled in the study. Common infections included diarrhea 68% and respiratory tract infections 48%. Gram negative bacteria constituted 60% (61) of the total isolates, Escherichia coli was the leading gram negative organism (45%). Gram positive bacteria constituted 40% (38) of the total isolates .Coagulase negative staphylococci species (CONS species) 31% (31) were the most common gram positive organisms. In vitro sensitivity by disk diffusion showed 64% and 61% sensitivity to Amikacin and Gentamycin. Susceptibility of isolates to Ciprofloxacin, Amoxycillin, Co-trimoxazole and Ampicillin was 53%, 29%, 25% and 13% respectively. Conclusion: Overwhelming resistance to WHO recommended antibiotics was seen in the study population. Diarrhea and respiratory tract infections were the commonest infections among the malnourished. E.coli was the leading organism. Most bacteria isolates were sensitive to Amikacin and Gentamicin. There is a need for re-evaluation of the WHO recommendations for management if infections in malnourished children.